Angiotensin 1–7 and the Non-Peptide MAS-R Agonist AVE0991 Inhibit Breast Cancer Cell Migration and Invasion - Mariam M. Alfoudiry; Maitham A. Khajah (Biomedicines)
Background: Endocrine resistance in breast cancer is associated with the epithelial-to-mesenchymal transition (EMT), resulting in enhanced cell proliferation, motility, and invasion and leading to a poor prognosis. There are few studies regarding the role of Angiotensin II (Ang II) and Angiotensin 1–7 (Ang 1–7) in relation to breast cancer, with contradictory outcomes. This study aims to investigate the expression of Ang 1–7 and MAS-R and evaluate the effects of Ang II, Ang 1–7, and the MAS-R agonist AVE0991 on EMT induction and reversal. Methods: The effects of Ang II and Ang 1–7 on normal and breast cancer cell lines were determined using various techniques for cell proliferation (MTT), motility (scratch assay), and invasion (Cultrex assay). Also, the expression/localization profiles of Ang 1–7 and its receptor (MAS-R), as well as various EMT markers, were determined using immunofluorescence, western blot, and ELISA. Results: Ang II significantly decreased the motility of the tested cell lines; however, it did not have a significant effect on their proliferation or invasion. The expression profiles of the tested EMT markers were not affected by Ang II treatment. The expression levels of Ang 1–7 and MAS-R were significantly higher in the normal breast epithelial cells and estrogen receptor ER compared to the ER+ breast cancer cells. Treatment with Ang 1–7 or the non-peptide MAS-R agonist AVE0991 significantly reduced the migration and invasion of the tested cell lines without modulating the tested EMT markers. Compared to Ang 1–7, AVE0991 exhibited a more prominent dose-dependent inhibitory effect on the proliferation, motility, and invasion of the ER− breast cancer cells. Conclusions: Ang 1–7 and AVE0991 play a promising therapeutic role in breast cancer, in part by reducing cell motility and invasion.